Effect of Different Doses and Times of FK506 on Different Areas of the Hippocampus in the Rat Model of Transient Global Cerebral Ischemia-Reperfusion - Zahra Nadia Sharifi; Hamid Zaferani Arani; Maedeh Olya; Hesam Adin Atashi; Shabnam Movassaghi (Neurology Research International)
Background. Stroke is a major worldwide problem that is leading to a high mortality rate in humans. Ischemia, as the most common type of stroke, is characterized by tissue damage that can occur due to insufficient blood flow to the brain even for a brief duration, leading to the release of inflammatory factors, cytokines, and free radicals. In this study, we investigated the effective dose and injection time of FK506 as an immunophilin ligand for providing a suitable effect on cells of CA2, CA3, and dentate gyrus of the hippocampus. Methods. In this in vivo study, a total of 48 male Wistar rats were divided into nine groups. The ischemia model was induced by the ligation of bilateral common carotid arteries. The doses of FK506 (3, 6, and 10 mg/kg) were administered intravenously (IV) at the beginning of reperfusion, followed by repeated injections (10 mg/kg) at 6, 24, 48, and 72 hours after ischemia, respectively. Brains were removed and prepared for Nissl staining and the TdT-mediated dUTP Nick End Labeling method. Results. Data showed that global ischemia did not decrease the number of viable pyramidal cells in CA2 and CA3 regions, but significant differences were observed in the number of viable granular cells and apoptotic bodies in the dentate gyrus between the control and ischemia groups. Repeated doses of 6 mg/kg of FK506 at an interval of 48 hours were deemed to be the suitable dose and best time of injection. Conclusions. It seems that FK506 can ameliorate the extent of apoptosis and may be a good candidate for the treatment of ischemia-induced brain damage.